Genotype-phenotype association and biochemical analyses of glucose-6-phosphate dehydrogenase variants: Implications for the hemolytic risk of using 8-aminoquinolines for radical cure - Sudsumrit, S; Chamchoy, K; Songdej, D; Adisakwattana, P; Krudsood, S; Adams, ER; Imwong, M; Leartsakulpanich, U; Boonyuen, U (Frontiers Media, 2022)
Background: Plasmodium vivax remains the malaria species posing a major threat to human health worldwide owing to its relapse mechanism. Currently, the only drugs of choice for radical cure are the 8-aminoquinolines (primaquine and tafenoquine), which are capable of killing hypnozoites and thus preventing P. vivax relapse. However, the therapeutic use of primaquine and tafenoquine is restricted because these drugs can cause hemolysis in individuals with glucose-6-phosphate dehydrogenase (G6PD) deficiency. This study aimed to assess and understand the hemolytic risk of using 8-aminoquinolines for radical treatment in a malaria endemic area of Thailand.